2006
DOI: 10.1080/09546630600823369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of psoriatic arthritis and psoriasis in dermatologists' offices

Abstract: Assessment for joint disease in psoriasis patients being treated at dermatology clinics may facilitate earlier psoriatic arthritis diagnosis and treatment initiation, which may prevent disability and other negative impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 28 publications
8
49
0
Order By: Relevance
“…However, these observations do not necessarily imply that severe skin disease is associated with more extensive joint involvement. Studies that have attempted to address this issue have been limited by small patient cohorts [8,9,10] or by pre-specified study entry criteria [1]. In particular, the phase IV open-label trial of etanercept reported by Gottlieb et al [1] excluded patients whose psoriasis involved <10% of the BSA, an important component of the PsA population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these observations do not necessarily imply that severe skin disease is associated with more extensive joint involvement. Studies that have attempted to address this issue have been limited by small patient cohorts [8,9,10] or by pre-specified study entry criteria [1]. In particular, the phase IV open-label trial of etanercept reported by Gottlieb et al [1] excluded patients whose psoriasis involved <10% of the BSA, an important component of the PsA population.…”
Section: Discussionmentioning
confidence: 99%
“…For most patients with PsA, psoriatic symptoms precede joint involvement [1]. Accordingly, dermatologists have a key role to play in the early recognition of PsA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. Gottlieb et al, 2006), and in general, the prevalence of arthritis in psoriasis patients is estimated to be approximately 30% (Gisondi et al, 2005;Zachariae et al, 2002).…”
Section: Psoriatic Arthritismentioning
confidence: 99%